(untitled) (Zoo Botanica, 2025)
Intercropping is an important component in cropping system research. It can improve crop productivity by utilizing a piece of land efficiently. It also strengthens the farmer’s capability towards growing crops to adapt to climate change impacts. Hence, a field experiment to identify the advantages of sunflower-cotton intercropping over solitary cropping through agronomic interactions in arid irrigated conditions was conducted in the crop season of year 2016 and 2017. The experiment was designed in RCBD with four replications. The experiment comprised four treatments; 75 cm sole planting of sunflower (P1), 75 cm sole planting of cotton (P2), 75 cm single row of sunflower with cotton (P3), and 112.50 cm double rows strip of sunflower with cotton (P4). Evaluations of planting patterns were performed based on several crop competition indices. Agronomic interactions revealed that sunflower-cotton single-row intercropping (P3) had advantages over solitary planting, due to its better yield of cotton (2444, 2383 kg ha-1) and sunflower (3055, 2752 kg ha-1), Land Equivalent Ratio (1.76, 1.73), Competitive Ratio (2.03, 2.01), significant Relative Crowding Coefficient (32.73, 15.37) and lower Aggressivity (0.16, -0.16; 0.10, -0.10) in year 2015 and 2016, respectively. The sunflower crop was more competitive than the cotton crop in planned planting patterns. Although the yield of intercrops was low compared to pure stands, the results obtained from competition indices attributed to better land use efficiency when the intercrops were sown in 75 cm spaced single rows with limited use of external inputs. Hence, it is concluded that this practice is economical and feasible for application at the farmer’s field for higher productivity of the cropping system